Analysis Of The Ability To Understand Mathematical Concepts As Seen In The Face Of Students' Self-Confidence In The Material On Numbers Round Grade VII l - Rachel Ulita; Golda Novatrasio Sauduran; Christina Purnamasari K. Sitepu (Jurnal Pendidikan, Sains Sosial, dan Agama, 2023)
This study aims to describe the relationship between self-confidence and students' mathematical conceptual understanding of integers in class VII-3 of SMPN 19 Medan in the 2025/2026 academic year. This study used a quantitative descriptive study using the Simple Random Sampling method, involving 32 students as a sample. The instruments used were a self-confidence questionnaire and a conceptual understanding ability test. Data were analyzed using Rank Correlation, a nonparametric method suitable for ordinal scale data. The analysis results showed a correlation coefficient (r-rank) of 0.889, indicating a very strong positive relationship between self-confidence and students' conceptual understanding. The higher the students' self-confidence, the better their mathematical conceptual understanding. Furthermore, the results of processing the questionnaire using a Likert scale showed an average achievement percentage of 65.09%, which is in the moderate category. This finding implies that although most students have fairly good self-confidence and conceptual understanding, efforts are still needed to achieve achievement in the high category.